Story-telling Silk Route Collapsing the Walls of Differences: An Analysis on Chitra Banerjee Divakaruni’s One Amazing Thing - Talukdar, Susmita (Literary Studies, 2016)
The article examines power of narrative/storytelling in developing collective force that would serve as survival strategy for facing catastrophe. In Divakaruni’s One Amazing Thing the nine characters, who are trapped by a major earthquake in the basement of a high-rise building of Indian visa office in US, go on telling his/her stories of their past, ‘one amazing thing’ of their lives that they have never been able to share with anyone. Like a very ancient story telling form e.g. the Panchatantra, stories lead to more stories. One story makes the listeners to muse about how it applies to their lives, and that ultimately leads them coming up with their own stories, the choice of which is influenced by the previous story. In their manner of telling stories, the characters feel strangely bound to each other, though they are so different from each other. It is the incredible power of storytelling that collapses the wall of several tags of identity, and brings together the strangers, who are stuck in one room due to natural disaster. Ironically the story takes place in a visa office that confirms one’s identity in terms of his/her nationality, race, ethnicity and similar others. It is a natural disaster that brings people from different origin closer to each other and it is the healing power of narrative/storytelling that dissolves all differences revealing what it means to be human.